Surface Energetics of Mycobacterium Tuberculosis – Macrophage Interactions - H, Achebe C.; E, Sinebe J.; L., Chukwuneke J.; S., Ejiofor O. (British Journal of Healthcare and Medical Research, 2016)
The surface thermodynamics of M-Tb/HIV-macrophage interactions were studied using the Hamaker coefficient concept as a surface energetics tool in determining the interaction processes. The surface interfacial energies were explained using van der Waals concept of particle - particle interactions. The method involved sputum sample collection, mycobacterium and macrophages structural studies, and the study of the mechanism of interaction of the bacterium and the macrophage. Twenty samples each of infected, uninfected and M-Tb/HIV co-infected sputum were collected. Each specimen was screened to determine the infection status using GeneXpert and Ziehl-Neelsen staining methods. The absorbance, ā, values of each specimen, for wavelength range of 230 – 950nm were measured using digital Ultraviolet Visible Spectrophotometer. From the absorbance data the variables (e.g. dielectric constant, etc.) required for computations were derived. MatLab software tools were employed in the mathematical analysis. The Hamaker constants, combined Hamaker coefficients and absolute combined Hamaker coefficients were obtained. The values of A132abs = 0.21631x10-21Joule and Ã132abs = 0.18825x10-21Joule were obtained for M-Tb and M-Tb/HIV infected sputum respectively. The implication of this result is the positive value of the absolute combined Hamaker coefficient which entails net positive van der waals forces demonstrating an attraction between M-Tb and the macrophage. This however, implies that infection is very likely to occur. It was also shown that in the presence of HIV, the interaction energy is reduced by 13% confirming adverse effects observed in HIV patients suffering from tuberculosis. The lower value for the combined Hamaker coefficient A131abs = 10165 x10-21Joule for the uninfected sputum samples is an indicator that a negative Hamaker coefficient is realistic. The desired outcome is that the bacteria do not adhere to the macrophage to avoid penetration, in which case a condition for rendering combined Hamaker coefficient negative is required. Thus, condition was sought for repulsion to occur and that condition was based on the value of A33 that would render the absolute combined Hamaker coefficient negative. To achieve the condition of A33 above, possible additive(s) in form of drugs to the sputum should be required.